Disruptive effects of nonylphenol on reproductive hormones, antioxidant enzymes, and histology of liver, kidney and gonads in Caspian trout smolts - Shirdel, Iman; Kalbassi, Mohammad Reza; Esmaeilbeigi, Milad; Tinoush, Boshra (Comparative biochemistry and physiology. Part C, Toxicology & pharmacology, 2020)
The endocrine-disrupting effect of pollutants such as alkylphenols has been considered a major concern during recent years. Although the effects of nonylphenol on the reproductive hormones of fish have been investigated in several studies, the effect of this endocrine disruptor on reproductive hormones of immature fish and salmonid smolts has been less addressed. The present work studied the effects of 1, 10 and 100 μg/l concentrations of nonylphenol on the levels of plasma reproductive hormones and liver antioxidant enzymes as well as on histopathology of reproductive and non-reproductive organs of male and female Caspian brown trout (Salmo trutta caspius) smolts after 21 days of exposure. The results of the present study showed that environmentally relevant concentrations of nonylphenol affected plasma levels of sex steroids; gonadotropins, phosphorus, estradiol to testosterone ratio, and also caused histopathological lesions in liver, kidney and testis tissues of immature Caspian brown trout during smolting. Nonylphenol significantly increased the levels of estradiol in plasma of both male and female smolts exposed to nonylphenol compared with the control groups. Exposure to nonylphenol decreased testosterone and FSH levels in both genders. It has also increased plasma levels of LH in females but did not affect LH levels in male fish. Liver SOD and CAT content was decreased in nonylphenol-exposed smolts. Therefore, the release of this economically valuable and endangered species into the rivers contaminated with nonylphenol should be avoided as it can have significant effects on the development and reproductive function of smolts.
Gesehen am 28.05.2020